SOSIALISASI PENTINGNYA BUDAYA MENABUNG SEJAK DINI DI KALANGAN PELAJAR DUSUN KUANG MAYUNG - Widiantari, Ni Wayan Ega; Sukendri, Nengah; Intaran, I Made; Purnamayasa, I Komang Widya (Universitas Pattimura, 2026)
A culture of saving is a positive behavior that is important to instill in children from an early age. In Kuang Mayung Hamlet, high levels of unplanned spending and a lack of understanding of financial management are real problems that need to be addressed. This activity aims to educate students about the importance of a culture of saving as a first step in developing a disciplined, responsible, and independent character in managing their finances. The methods used in this activity included an educational approach through counseling from BRI Bank, interactive discussions, and simple savings practices tailored to the students' age level. The results of this activity showed a 40% increase in students' understanding of the importance of saving after participating in the socialization, as measured by pre- and post-training questionnaires. Evaluation was based on changes in savings attitudes and behavior, as well as participation levels in the activities. It is hoped that by instilling a culture of saving from an early age, students can develop a thrifty mindset, better plan for the future, and avoid unhealthy consumer behavior. Overall, this activity is expected to have a positive impact in supporting the development of healthy financial character among students in Kuang Mayung Hamlet. Instilling the values of saving is very important as part of efforts to create a young generation that is smart and wise in financial management